2011
DOI: 10.1016/j.lfs.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial involvement in carbachol-induced intracellular Ca2+ mobilization and contraction in rat gastric smooth muscle

Abstract: Taken together our results indicate that CCh induces release of Ca2+ from intracellular stores, which may be modulated by mitochondria. Thus, mitochondria participate of the intracellular Ca2+ homeostasis in muscarinic contraction in gastric fundus smooth muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
1
8
0
1
Order By: Relevance
“…Mitochondria were shown to modulate control IP 3 -evoked Ca 2+ release by operating within an IP 3 R cluster, and when mitochondrial Ca 2+ uptake was prevented, a localised Ca 2+ release from an IP 3 R (a Ca 2+ puff) was inhibited (Fig. 3) [17,22,57,76,78]. The results were consistent with Ca 2+ uptake by mitochondria limiting a negative feedback effect of Ca 2+ on the IP 3 R cluster.…”
Section: Mitochondrial Regulation Of Smooth Muscle Ca 2+ Signalssupporting
confidence: 69%
See 2 more Smart Citations
“…Mitochondria were shown to modulate control IP 3 -evoked Ca 2+ release by operating within an IP 3 R cluster, and when mitochondrial Ca 2+ uptake was prevented, a localised Ca 2+ release from an IP 3 R (a Ca 2+ puff) was inhibited (Fig. 3) [17,22,57,76,78]. The results were consistent with Ca 2+ uptake by mitochondria limiting a negative feedback effect of Ca 2+ on the IP 3 R cluster.…”
Section: Mitochondrial Regulation Of Smooth Muscle Ca 2+ Signalssupporting
confidence: 69%
“…Several early studies have shown that Ca 2+ increases evoked by IP 3 -generating agonists were almost fully inhibited when mitochondrial Ca 2+ uptake was prevented [17,22,57,76,78], i.e. mitochondria appeared to determine whether or not a Ca 2+ signal occurred at all.…”
Section: Mitochondrial Regulation Of Smooth Muscle Ca 2+ Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…CBX and 18βGA have been reported to collapse the mitochondrial membrane potential (ΔΨ M ) (Salvi et al, 2005; Wang, Wong, Feng, & Zhang, 2014). Collapse of ΔΨ M has widespread effects on cell function, including on the regulation of IP 3 ‐evoked Ca 2+ release (Alexander, Kelly et al, 2019; Correa et al, 2011; Csordas et al, 2006; Narayanan, Xi, Pfeffer, & Jaggar, 2010; Olson, Chalmers, & McCarron, 2010; Rizzuto, Brini, Murgia, & Pozzan, 1993; Rizzuto et al, 1998; Sward, Dreja, Lindqvist, Persson, & Hellstrand, 2002; Szado et al, 2003). To determine if the ΔΨ M was altered by the drugs, mitochondria were visualised using the membrane potential indicator TMRE (120 nM, 5 min; Figure 9a) and the effects of CBX and 18βGA on ΔΨ M were examined.…”
Section: Resultsmentioning
confidence: 99%
“…Як вста-новлено дослідженнями останніх років, в основі генерації спонтанної деполяриза-ції пейсмекерних ІКК лежать процеси перерозподілу іонів Са 2+ між внутрішньоклі-тинними депо (так звані кальцієві мікродомени): Са 2+ , вивільняючись із саркоплаз-матичного ретикулуму (СР), захоплюється мітохондріями, і саме це зниження кон-центрації Са 2+ призводить до активації пейсмекерних катіонних струмів у плазма-тичній мембрані ІКК [22,36]. Робота Са 2+ -уніпортера мітохондрій є потенціал-за-лежною: у разі деполяризації внутрішньої мембрани мітохондрій депонування відбувається з меншою ефективністю і супроводжується пригніченням спонтанної активності гладеньких м'язів, і навпаки, під час її фармакологічної гіперполяризації спонтанна активність ІКК посилюється [8]. Поряд із тим, на ізольованих міоцитах матки щурів було з'ясовано, що окремі каліксарени, зокрема і С-99, на тлі дії уабаї-ну спричиняють суттєву поляризацію внутрішньої мітохондріальної мембрани [9].…”
Section: особливості спонтанної скоротливої активності за наявності кunclassified